Իրավունքի գլոբալացման եղանակների և ձևերի առանձնահատկությունները - Արեն Տեր-Բալյան (ՀՀ ԳԱԱ հրատ.)
В данной научной статье автор, на основе изучения глобализации права,представляет особенности форм и видов глобализации права. В частности, раскрываются особенности гармонизации, унификации, трансформации права, а так же и типовых законов в современном демократическом правовом государстве. In this scientific article, the author, based on the study of the globalization of law, presents the features of the forms and types of globalization of law. In particular, the features of harmonization, unification, transformation of law, as well as model laws in a modern democratic state are revealed.
Keywords: Law